Decentralization in developing countries : a review of recent experience - Rondinelli, Dennis A.; Nellis, John R.; Cheema, G. Shabbir (Washington, D.C., U.S.A. : World Bank, 1983)
This study is one in a series of World Bank Staff Working Papers devoted to issues of development management. The thirteen papers cover topics ranging from comprehensive surveys of management issues in different types of public institutions to broad overviews of such subjects as planning, management, training, technical assistance, corruption , and decentralization
Bibliography: p. 94-99.
osc 31/01/2019
Loans
Keywords: Decentralization in government; Developing countries